2019
DOI: 10.1152/ajplung.00441.2018
|View full text |Cite
|
Sign up to set email alerts
|

CARM1 regulates senescence during airway epithelial cell injury in COPD pathogenesis

Abstract: Chronic obstructive pulmonary disease (COPD) is a life-threatening lung disease. Although cigarette smoke was considered the main cause of development, the heterogeneous nature of the disease leaves it unclear whether other factors contribute to the predisposition or impaired regeneration response observed. Recently, epigenetic modification has emerged to be a key player in the pathogenesis of COPD. The addition of methyl groups to arginine residues in both histone and nonhistone proteins by protein arginine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Coactivator-associated arginine methyltransferase-1 (CARM1) regulates airway epithelial cell injury in COPD progression. 29 Complete loss of CARM1 leads to disrupted differentiation and maturation of epithelial cells and promote the development of emphysema. 30 Our previous work also shown that dysregulation of DNA methyltransferase DNMT1 involved in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Coactivator-associated arginine methyltransferase-1 (CARM1) regulates airway epithelial cell injury in COPD progression. 29 Complete loss of CARM1 leads to disrupted differentiation and maturation of epithelial cells and promote the development of emphysema. 30 Our previous work also shown that dysregulation of DNA methyltransferase DNMT1 involved in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke can cause inflammation, which is an important injury factor in lung diseases such as COPD ( 41 ). The damage to the lungs caused by cigarette smoke is most directly reflected in the injury of bronchial epithelial cells and alveolar epithelial cells ( 42 ). Bronchial epithelial cells are one of the key cell types that mediate inflammation and the 16HBE cell line is a common cell line used to study COPD pathogenesis in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The naphthalene-induced airway injury used in this study results in specific ablation of club cells of the airway only and may not fully recapitulate an epithelial lesion. However, previous studies have demonstrated that club cells account for 15% of proliferating airway epithelial cells in the terminal bronchioles and, thus, are vital for maintaining the distal airways after injury ( 69 , 96 ). Therefore, we consider naphthalene a suitable model for studying airway injury in a murine model.…”
Section: Discussionmentioning
confidence: 99%